HIV/HCV/HBV testing in the emergency department: a feasibility and seroprevalence study. (28th February 2018) - Bradshaw, D; Rae, C; Rayment, M; Turner, N; Turner, R; Pickard, G; Pillay, K; Roberts, P; Foxton, M; Sullivan, AK
Abstract : Objectives: The aims of this study were to to assess the feasibility of simultaneous testing for the blood‐borne viruses (BBV), HIV, hepatitis C (HCV) and hepatitis B (HBV), in the Emergency Department (ED) and ascertain the seroprevalence for these three viruses in this setting. Methods: A pilot BBV testing program was undertaken as part of routine clinical care in the ED. All ED attendees aged between 16 and 65 years old who were able to consent were tested over a 55 week period on an opt out basis. Patients with positive test results were linked to clinical services. Interventions aimed at improving testing rates were implemented and evaluated by quality improvement (QI) methodology. Results: Of 25, 520 age‐eligible ED attendees, 6108 (24%) underwent BBV testing; an additional 1160 (4.5%) underwent a standalone HIV test (total of 7268 (28%) individuals).There were 83/7268 (1.1%) non‐negative (ie reactive or equivocal) results for HIV and 103/6108 (1.7%) and 32/6108 (0.52%) for anti‐HCV IgG and HBsAg, respectively. Of these, 12 (0.17%), 16 (0.26%) and 8 (0.13%) were new reactive tests for HIV, HCV and HBV, respectively, which were able to be confirmed on a second test. Specific QI interventions led to temporary increases in testing rates. Conclusions: An opt out BBV testing program in the ED is feasible and effective at finding new cases. However, the testing rate was low at 24%. Although QI interventions led to some improvement in testing rates, further studies are required to identify ways to achieve sustained increases in testing in this setting.